A first course in mathematical physics - Colm, Whelan T. (Weinheim, Germany Wiley-VCH Verlag GmbH & Co. KGaA, 2016)
The book assumes next to no prior knowledge of the topic. The first part introduces the core mathematics, always in conjunction with the physical context. In the second part of the book, a series of examples showcases some of the more conceptually advanced areas of physics, the presentation of which draws on the developments in the first part.
Includes bibliographical references (pages 309-310) and index.
Keywords: Mathematical physics